Flaxseed oil supplementation improves intestinal function and immunity, associated with altered intestinal microbiome and fatty acid profile in pigs with intrauterine growth retardation. Issue 12 (7th November 2019) - Che, Lianqiang; Zhou, Qiang; Liu, Yan; Hu, Liang; Peng, Xie; Wu, Cheng; Zhang, Ruinan; Tang, Jiayong; Wu, Fali; Fang, Zhengfeng; Lin, Yan; Xu, Shengyu; et al.
Abstract : Flaxseed-supplemented diet could improve intestinal function and immunity of both IUGR and NBW pigs, associated with the altered gut microbiome and mucosal fatty acid profile. Abstract : Flaxseed oil (FO), enriched in n-3 polyunsaturated fatty acids (PUFAs), is an important oil source for intestinal development and health. We aimed to study the different effects of FO versus soybean oil (SO) on growth, intestinal health and immune function of neonates with intrauterine growth retardation (IUGR) using a weaned piglet model. Forty pairs of male IUGR and normal birth weight piglets, weaned at 21 ± 1 d, were fed diets containing either 4% FO or SO for 3 weeks consecutively. Growth performance, nutrient digestibility and intestinal function parameters, immunology and microbiota composition were determined. IUGR led to a poor growth rate, nutrient digestibility and abnormal immunology variables, whereas feeding FO diet improved systemic and gut immunity, as indicated by increased plasma concentration of immunoglobulin G and decreased CD3 + CD8 + T lymphocytes, and down-regulated intestinal expression of genes ( MyD88, NF-κB, TNF-α, IL-10 ). Although IUGR tended to decrease villous height, feeding FO diet tended to increase the villi–crypt ratio and up-regulated expressions of tight junction genes ( Claudin-1 and ZO-1 ), together with increased mucosa contents of n-3 PUFAs and a lower Σn-6/Σn-3 ratio. Besides, FO diet decreased the abundance of pathogenic bacteria Spirochaetes, and increased phylum Actinobacteria, and genera Blautia and Bifidobacterium in colonic digesta. Our findings indicate that IUGR impairs growth rate, nutrient digestibility, and partly immunology variables, whereas feeding FO-supplemented diet could improve intestinal function and immunity of both IUGR and NBW pigs, associated with the altered gut microbiome and mucosal fatty acid profile.